Low-frequency ultrasound responsive release and enhanced antibacterial efficacy of sulfamethoxazole decked silver nanocomposite. (1st February 2021) - Saraf, Aparna; Padave, Omkar; Sharma, Shweta; Jha, Pamela; Jobby, Renitta; Ali, Ahmad; Sachar, Shilpee
Graphical abstract: Highlights: Ultra-sonic mediated triggered release of SMX from the synthesized SMX-Silver nanocomposite. Synthesized nanocomposite showed long-term biocompatibility toward vital proteins. SMX-Silver nanocomposite showed enhanced antibacterial activity against gram positive and gram negative bacteria. Abstract: A new theranostic formulation for effective Sulfamethoxazole (SMX) delivery is designed using silver nanoparticles. Sulfamethoxazole-Silver nanocomposite (SMX-AgNP) was formulated by chemical reduction method and was characterized via X-ray diffraction [XRD], thermogravimetric analysis [TGA], differential scanning calorimetry [DSC], fourier transform infrared spectroscopy [FTIR] and scanning electron microscopy [SEM]. The drug was released via low frequency ultrasound mediation and thus can be helpful in achieving targeted release for SMX at desired sites. Circular dichroism [CD] studies were done to assess the effects of the synthesized composites on the vital proteins viz., serum proteins and collagen. Synergism of silver nanoparticles (AgNPs) and SMX was found to be effective for the gram positive and gram-negative bacteria. Significant bacterial activity was shown by the composite with better MICs (minimum inhibitory concentration) and MBCs (minimum bactericidal concentration) [<50%] values in comparison to the SMX alone. Thus, the low-frequency ultrasound assisted controlled release of the SMX from the AgNPs along with enhanced antibacterial activity can open new avenues for the treatment of bacterial infections at targeted site.